Learning to see like an expert: On the practices of professional vision and visual expertise - Gegenfurtner Andreas; Lehtinen Erno; Helle Laura; Nivala Markus; Svedström Erkki; Säljö Roger (ELSEVIER SCI LTD, 2022)
Goodwin's notion of professional vision suggests that learning to see in professionally relevant ways includes appropriating the visual practices within a domain. This observational study aimed to analyze how experts communicate these visual practices to novices to help them make meaning of domain-specific representations. Informed by a sociocultural perspective and founded on conversation analysis and ethnomethodology, video-recorded discourse and interaction between one expert in radiology and four laypeople were analyzed. The findings indicate three visual practices the medical expert uses to teach the novices how to see: highlighting, rotating, and zooming. The qualitative analyses suggest that learning to see professionally can be described as the mastering of expert practices in a focal domain. Implications for visual expertise research are discussed.